Ceramic substrate and electrostatic chuck
By using high-purity alumina ceramics and optimized conductive pattern composition, the problem of reducing insulation resistance of the ceramic substrate at high temperature is solved, the adhesion strength between the ceramic and the conductive body is improved, and the stable performance of the electrostatic chuck is achieved.
Patent Information
- Application Number
- CN201910837265.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-08-09
- Filing Date
- 2019-09-05
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2039-09-05
AI Technical Summary
The insulation resistance value of the existing ceramic substrates tends to decrease when the temperature rises, and good bonding strength between the ceramic and the conductor tungsten cannot be obtained during firing, which affects the performance of the electrostatic chuck.
Using an alumina ceramic substrate with a purity of 99.5% or more, by adding nickel oxide and silica to the conductive pattern, a sintered body including tungsten, nickel oxide and alumina is formed, thereby improving the sintering property and bonding strength, and sintering is carried out during sintering. Control the amount of addition during the manufacturing process to optimize the granularity.
It realizes the maintenance of a high insulation resistance value under a high temperature environment, improves the bonding strength between the ceramic substrate and the conductor, avoids the need for sintering agent, and ensures the stable performance of the electrostatic chuck.
Smart Images

Figure CN110880471B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a ceramic substrate and an electrostatic chuck. Background Art
[0002] In the background art, a semiconductor manufacturing apparatus for processing substrates such as semiconductor wafers has an electrostatic chuck for holding semiconductor wafers. Semiconductor manufacturing apparatus is, for example, a film forming apparatus such as a CVD apparatus or a PVD apparatus, a plasma etching apparatus, etc. The electrostatic chuck has a mounting platform for a ceramic substrate and a conductor pattern arranged inside the mounting platform. Utilizing this configuration, the electrostatic chuck can hold the substrate on the mounting platform using the conductor pattern as an electrostatic electrode. For example, the conductor pattern is formed in such a manner that a conductive paste containing a high melting point material such as tungsten is used and fired simultaneously with the ceramic substrate (for example, see PTL 1 and PTL 2). Incidentally, a ceramic substrate for a semiconductor device is also formed in a similar or identical manner (see, for example, JP-A-H4-331779 and JP-A-H6-290635).
[0003] The above-mentioned electrostatic chuck is formed in such a way that a conductive paste is printed on a green sheet and the green sheet and the conductive paste are sintered at the same time. For example, it is assumed that the green sheet is made of a ceramic (alumina ceramic) containing aluminum oxide (alumina) as a main component, and the conductive paste is made of tungsten. In this case, a sintering agent (such as silicon dioxide, magnesium oxide, calcium oxide, yttrium oxide, etc.) is usually contained in the alumina ceramic. Ceramics containing a sintering agent in this way have an insulation resistance value: when the temperature of the use environment increases, its insulation resistance value tends to decrease. Therefore, it is desirable to use alumina ceramics without a sintering agent having a lower temperature dependence of insulation resistance. However, since there is no sintering agent that can become a liquid phase during firing, it may not be possible to obtain the bonding strength between the ceramic and the tungsten used as a conductor. Summary of the Invention
[0004] Some embodiments provide a ceramic substrate.
[0005] The ceramic substrate includes:
[0006] a substrate body; and
[0007] A conductor pattern is provided in the substrate body.
[0008] The substrate body is made of ceramic containing aluminum oxide.
[0009] The conductor pattern is a sintered body containing tungsten as a main component and further containing nickel oxide, aluminum oxide, and silicon dioxide. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1is a schematic cross-sectional view of an electrostatic chuck according to a first embodiment;
[0011] Figure 2 is a schematic plan view of an electrostatic chuck;
[0012] Figure 3 is a perspective view showing a manufacturing process of an electrostatic chuck;
[0013] Figure 4 is a perspective view showing a manufacturing process of an electrostatic chuck;
[0014] Figure 5 is a perspective view showing a manufacturing process of an electrostatic chuck;
[0015] Figure 6 is a perspective view showing a manufacturing process of an electrostatic chuck;
[0016] Figure 7A is a perspective view showing a scratch test;
[0017] Figure 7B is a perspective view showing a peel test;
[0018] Figure 8 1 is an explanatory diagram showing the evaluation results of the addition amount, resistivity, sinterability, and adhesiveness of each sample;
[0019] Figure 9A and Figure 9B is a cross-sectional image showing the ceramic and electrodes of the sample;
[0020] Figure 10 is the secondary electron image of the sample being analyzed;
[0021] Figure 11 is a cross-sectional image showing the oxygen analysis results of the sample;
[0022] Figure 12 is a cross-sectional image showing the tungsten analysis results of the sample;
[0023] Figure 13 is a cross-sectional image showing the nickel analysis results of the sample;
[0024] Figure 14 is a cross-sectional image showing the aluminum analysis results of the sample;
[0025] Figure 15 is a cross-sectional image showing the silicon analysis results of the sample;
[0026] Figure 16 is an explanatory diagram showing test results;
[0027] Figure 17 is an explanatory diagram showing the relationship between temperature and resistance value of ceramics;
[0028] Figure 18 is a schematic cross-sectional view of a semiconductor device package according to a second embodiment; and
[0029] Figure 19 is a schematic plan view of a semiconductor device package. DETAILED DESCRIPTION
[0030] Various embodiments will be described below.
[0031] Incidentally, some of the drawings show component elements in an enlarged manner to facilitate understanding of the components. The dimensional ratios of the component elements in some of the drawings differ from the actual dimensional ratios or from the dimensional ratios in other drawings or other drawings. Furthermore, in the cross-sectional views, some component elements that should be hatched are not hatched to facilitate understanding of the components.
[0032] (First embodiment)
[0033] Figure 1 FIG. 2 shows a schematic cross-sectional view of an electrostatic chuck according to a first embodiment. Figure 1 As shown, the electrostatic chuck 1 has a base plate 10 and a mounting table 20 arranged on the base plate 10. The mounting table 20 is fixed to the upper surface of the base plate 10 by an adhesive such as silicone resin. Incidentally, the mounting table 20 may be fixed to the base plate 10 by screws.
[0034] The base plate 10 is made of, for example, a metal material such as aluminum or cemented carbide, or a composite material comprising a metal and ceramic material. For example, in order to improve usability, ease of processing, and excellent thermal conductivity, a material is used that uses aluminum or an aluminum alloy and has its surface treated with an alumite film (to form an insulating layer). For example, a refrigerant (gas, cooling water, etc.) supply path may be provided in the base plate 10 for cooling the substrate W mounted on the upper surface of the mounting table 20. The substrate W is, for example, a semiconductor wafer.
[0035] The mounting stage 20 has a substrate body 21 , and an electrostatic electrode 22 and a heating element 23 provided inside the substrate body 21 .
[0036] The substrate body 21 is formed into a disk shape according to the shape of the substrate W. The substrate body 21 is made of ceramic containing aluminum oxide (Al2O3). "Ceramic containing aluminum oxide" refers to ceramic to which no other inorganic components are added except for aluminum oxide. The purity of aluminum oxide used for the substrate body 21 made of ceramic is preferably 99.5% or more. A purity of 99.5% or more means that the substrate body 21 is formed without adding any sintering agent. In addition, a purity of 99.5% or more also means that the substrate body 21 may contain undesirable impurities during the manufacturing process, etc. The relative density of the substrate body 21 is preferably 98% or more. Specifically, the relative density of the substrate body 21 relative to ceramic containing only aluminum oxide is preferably 98% or more. The average particle size of the aluminum oxide used for the substrate body 21 is preferably not less than 1.0 μm and not more than 3.0 μm.
[0037] As a method for manufacturing the mounting table 20, the metal material for the electrostatic electrode 22 and the electric heating material for the heating element 23 are interposed between green sheets, and the resulting layered body is sintered. Thus, the mounting table 20 can be obtained in which the electrostatic electrode 22 and the heating element 23 are provided in the substrate body 21.
[0038] The electrostatic electrode 22 is a conductive body formed into a film shape. The electrostatic electrode 22 according to the present embodiment is a bipolar type and has a first electrostatic electrode 22a and a second electrostatic electrode 22b. Incidentally, a monopolar type electrostatic electrode consisting of one electrostatic electrode can be used as the electrostatic electrode 22. A conductive paste containing tungsten (W) as a main component and added with nickel oxide (NiO), aluminum oxide, and silicon dioxide (SiO2) can be used as the material of the electrostatic electrode 22.
[0039] The heating element 23 is arranged below the first electrostatic electrode 22a and the second electrostatic electrode 22b. The heating element 23 is a conductive body formed into a film. The heating element 23 is provided as a plurality of heating electrodes, and the plurality of heating electrodes can independently control the heating of a plurality of planar areas (heating areas) of the substrate body 21. Incidentally, the heating element 23 can be provided as a single heating electrode. A conductive paste containing tungsten (W) as a main component and added with nickel oxide (NiO), aluminum oxide, and silicon dioxide (SiO2) can be used as the material of the heating electrode 23.
[0040] like Figure 2 As shown, in the electrostatic chuck 1, the mounting table 20 is arranged on the disk-shaped base plate 10 so that the outer periphery of the base plate 10 is exposed around the mounting table 20. In the outer periphery of the base plate 10, mounting holes 11 for connecting the electrostatic chuck 1 to the chamber of the semiconductor manufacturing equipment are arranged along the outer periphery. In addition, the middle portion of each of the mounting table 20 and the base plate 10 has a plurality of ( Figure 1There are three lift pin openings 12. Lift pins for moving the substrate W in the up and down directions are inserted into the lift pin openings 12. When the substrate W is lifted from the mounting table by the lift pins, the substrate W can be automatically transported by the transport device.
[0041] like Figure 1 As shown, a substrate W is mounted on the mounting table 20 in the electrostatic chuck 1 according to this embodiment. A positive (+) voltage is applied to the first electrostatic electrode 22a, while a negative (-) voltage is applied to the second electrostatic electrode 22b. As a result, positive (+) charges accumulate in the first electrostatic electrode 22a, while negative (-) charges accumulate in the second electrostatic electrode 22b. Consequently, negative (-) charges are induced in the portion Wa of the substrate W corresponding to the first electrostatic electrode 22a, and positive (+) charges are induced in the portion Wb of the substrate W corresponding to the second electrostatic electrode 22b.
[0042] When the substrate W, the electrostatic electrode 22, and the ceramic portion 24 of the mounting table 20 (substrate body 21) disposed between the substrate W and the electrostatic electrode 22 are considered as a capacitor, the ceramic portion 24 corresponds to a dielectric layer. The substrate W is electrostatically attracted to the mounting table 20 by utilizing the Coulomb force generated between the electrostatic electrode 22 and the substrate W via the ceramic portion 24. A predetermined voltage is applied to the heating element 23, allowing the mounting table 20 to be heated by the heating element 23. The temperature of the mounting table 20 is utilized to control the substrate W to a predetermined temperature. The heating temperature of the electrostatic chuck 1 is set within a range of 50°C to 200°C, for example, to 150°C.
[0043] (Manufacturing Method)
[0044] Next, a method for manufacturing the aforementioned mounting table 20 will be described. First, as Figure 3 As shown, green sheets 51 to 53 made of ceramic material and organic material are prepared. Each of the green sheets 51 to 53 is formed into a rectangular plate. The ceramic material of the green sheets 51 to 53 contains alumina and does not contain any sintering agent.
[0045] In the green sheet 51, the organic components are removed and the ceramic material is sintered to be densified. Therefore, the obtained green sheet 51 is used as the substrate body 21 to be mounted. Figure 1 The green sheet 52 is fired to form a portion of the substrate body 21 between the electrostatic electrode 22 and the heating element 23 so that a Figure 1 The electrostatic electrode 22 shown in FIG. The green sheet 53 is fired to form a portion of the substrate body 21 to be bonded to the base plate 10 so that a Figure 1 The heating element 23 is shown in FIG.
[0046] Next, a conductor pattern 54 is formed on the upper surface of the green sheet 52 by, for example, a printing method (screen printing) using a conductive paste. The conductive paste contains tungsten as a main component and also contains a mixture of nickel oxide, aluminum oxide, silicon dioxide, and an organic material. In a step described later, the conductor pattern 54 is fired to form a conductive paste. Figure 1 The electrostatic electrode 22 is shown. Incidentally, a conductor pattern 54 may be formed on the lower surface of the green sheet 51 described above.
[0047] The conductive paste used to form the conductor pattern 54 contains tungsten as a main component and also contains a mixture of nickel oxide, aluminum oxide, silicon dioxide, and an organic material. The amount of nickel oxide added relative to tungsten is preferably 0.2 weight percent or more and 1.0 weight percent or less. In order to improve the sintering properties of tungsten, it is preferred to add nickel oxide in an amount of 0.2 weight percent or more. On the other hand, when nickel oxide is added in an amount of 5 weight percent or more, the tungsten crystals become too large to obtain sufficient adhesion between the electrostatic electrode 22 and the substrate body 21. After the conductive paste and the green sheet are simultaneously fired, the average particle size of the tungsten can be 0.5 μm or more and 3.0 μm or less, and the average particle size of the nickel oxide can be 5.0 μm or more and 15.0 μm or less.
[0048] The amount of aluminum oxide added relative to tungsten is preferably 0.2 weight percent or more and 3.0 weight percent or less. To improve adhesion between the electrostatic electrode 22 and the substrate body 21, which is made of a ceramic containing aluminum oxide, it is preferable to add at least 0.2 weight percent of aluminum oxide. On the other hand, adding more than 3.0 weight percent of aluminum oxide reduces sinterability and increases resistivity. After simultaneously firing the conductive paste and green sheet, the average particle size of the aluminum oxide can be 1.0 μm or more and 4.0 μm or less.
[0049] The amount of silicon dioxide added relative to tungsten is preferably 0.2 weight percent or more and 3.0 weight percent or less. Silicon dioxide becomes a liquid phase during firing. To improve the sintering properties of tungsten and the adhesion between the electrostatic electrode 22 and the substrate body 21, it is preferable to add silicon dioxide in an amount of 0.2 weight percent or more. On the other hand, when more than 3.0 weight percent of silicon dioxide is added, the sintering properties and adhesion are reduced. In addition, the resistivity increases. After the conductive paste and the green sheet are simultaneously fired, the average particle size of the silicon dioxide can be 1.0 μm or more and 12.0 μm or less.
[0050] Next, a conductor pattern 55 is formed on the upper surface of the green sheet 53 by, for example, a printing method (screen printing) using a conductive paste. The conductive paste used to form the conductor pattern 55 can use the same material as the conductive paste used to form the above-mentioned conductor pattern 54. In a step described later, the conductor pattern 55 is fired to form the heating element 23. Incidentally, the conductor pattern 55 can also be formed on the lower surface of the above-mentioned green sheet 52.
[0051] Next, if Figure 4 As shown, the green sheets 51 to 53 are stacked on each other to form a structure 71a. The green sheets 51 to 53 are pressed while being heated so that the green sheets 51 to 53 are bonded to each other.
[0052] Next, if Figure 5 As shown in FIG. 1 , the outer periphery of the structure 71a is cut to form a disk-shaped structure 71b. Next, the structure 71b is fired to obtain Figure 6 The temperature during firing is, for example, 1600°C. Figure 3 and Figure 4 The electrostatic electrode 22 and the heating element 23 are obtained by the conductor patterns 54 and 55 shown in FIG. Figure 1 ) is built into a ceramic substrate 72a. Such a ceramic substrate 72a can be machined in a variety of ways.
[0053] For example, the upper and lower opposite surfaces of the ceramic substrate 72a are polished to form the mounting surface and the bonding surface. Figure 1 The lift pin opening portion 12 is shown in FIG.
[0054] Through the above-described process, the mounting table 20 is obtained.
[0055] (Effect)
[0056] (Production of samples)
[0057] manufacture Figure 7A Sample 80 shown in . Sample 80 has a ceramic substrate 81 and a conductor pattern 82 provided on the upper surface of the ceramic substrate 81. The ceramic substrate 81 is made of a ceramic containing aluminum oxide. In addition, the ceramic substrate 81 has a raw material composition that does not contain any sintering agent. The purity of the aluminum oxide in the ceramic substrate 81 is 99.5% or more. The conductor pattern 82 is formed by a conductive paste containing tungsten or a conductive paste containing tungsten as a main component and to which the addition amounts of nickel oxide, aluminum oxide and silicon dioxide have been adjusted. The conductive paste is printed on a green sheet and then fired integrally and simultaneously. As a result, sample 80 is formed. In the sintered ceramic substrate 81, the average particle size of the aluminum oxide is in the range of 1.0 μm to 3.0 μm.
[0058] During the peel test, if Figure 7B As shown, a ring 83 made of kovar alloy is heated and bonded to the upper surface of the conductor pattern 82 of the sample 80 by means of a copper-containing silver solder. A tensile testing device is fixed to the ceramic substrate 81, one end of the ring 83 is pulled up, and the test force with which the conductor pattern 82 can be peeled off from the ceramic substrate 81 is recorded.
[0059] Figure 8 The figures show the amounts (weight percentages) of nickel oxide (NiO), aluminum oxide (Al2O3), and silicon dioxide (SiO2) added to the conductive paste used to form the conductor pattern 82 of each sample 80 manufactured by the present inventors, the resistivity (Ωm) of the conductor pattern 82, and the evaluation results of the sintering and adhesion properties of the conductor pattern 82. For the conductor pattern 82 of each manufactured sample 80, the sintering properties were evaluated by a scratch test (scratch test), and the adhesion properties were evaluated by a peel test. Incidentally, in the following description, samples No. 1 to No. 20 will be referred to as samples 1 to 20.
[0060] Sample 1 includes a conductor pattern 82 formed by using a conductive material containing tungsten but without adding (i.e., not containing) any of nickel oxide, aluminum oxide, and silicon dioxide. In Sample 1, the resistivity of the conductor pattern 82 is 2.85×10 -7 [Ωm]. Incidentally, the resistivity of tungsten is 5.29×10 -8 [Ωm].
[0061] Sample 1 was produced by printing a conductive paste on a green sheet and firing the green sheet and paste. The green sheet was made of aluminum oxide and did not contain any sintering agent. The conductive paste was made solely of tungsten. In Sample 1, the green sheet and the conductive paste contained no liquid component. Therefore, the tungsten contained in the conductive paste was not fired, and the strength of the conductive pattern 82 could not be achieved. Furthermore, adhesion between the ceramic substrate 81 and the conductive pattern 82 could not be achieved.
[0062] Each of Samples 2 to 20 includes a conductor pattern formed using a conductive paste. The conductive paste contains tungsten as a main component and is added with nickel oxide, aluminum oxide, and silicon dioxide. Samples 3 to 12 and Samples 14 to 20 are samples as follows: each sample includes a conductor pattern 82 using a conductive paste having the above-mentioned suitable composition (content). In each of Samples 3 to 12 and Samples 14 to 20, the sinterability of the conductor pattern 82 and the adhesion between the ceramic substrate 81 and the conductor pattern 82 were evaluated as excellent.
[0063] For Sample 2, a conductive paste was used in which nickel oxide, aluminum oxide, and silicon dioxide were each added in an amount of 0.1 weight percent. For Sample 13, a conductive paste was used in which nickel oxide was added in an amount of 0.1 weight percent, and aluminum oxide and silicon dioxide were each added in an amount of 1 weight percent. Due to the small amount of nickel oxide added (0.1 weight percent), the sinterability of tungsten was low, resulting in a poor evaluation.
[0064] Incidentally, in each of the conductor patterns 82 whose sinterability was poor (for each of Sample 1, Sample 2, and Sample 13 evaluated as poor), the test piece for the peel test could not be attached to the conductor pattern 82. Therefore, the adhesiveness of the conductor pattern 82 could not be evaluated by the tensile test.
[0065] Figure 9A The SEM image of the sample is shown, in which the conductive paste is printed on the front side of the green sheet and fired integrally and simultaneously. The conductive paste contains tungsten as a main component and is added with 0.5 weight percent nickel oxide, 2.0 weight percent aluminum oxide, and 2.0 weight percent silicon dioxide. The green sheet forms the above-mentioned ceramic substrate 81. Figure 9A , the conductor pattern 82 is arranged in the middle portion, and the ceramic substrate 81 is arranged on the lower side of the conductor pattern 82. In this sample, it can be confirmed that the conductor pattern 82 has excellent sinterability.
[0066] Figure 9B An SEM image of a sample is shown in which the electrical conductor pattern 82 is formed by using an additive-free conductive material made of tungsten. In this sample, the electrical conductor pattern 82 has low sinterability and low strength.
[0067] Analyzed by EPMA (Electron Probe Micro Analyzer) Figure 9A The samples shown in . Figure 10 is a secondary electron image of the sample being analyzed.
[0068] Figure 11 This is a cross-sectional image showing the results of oxygen analysis of the sample. Oxygen is present in both ceramic substrate 81 and conductor pattern 82. Oxygen is present in almost the same locations as aluminum and silicon (described later), and therefore, aluminum and silicon are found to exist as oxides even after combustion. Figure 12 This is a cross-sectional image showing the tungsten analysis results for the sample. Tungsten is localized within conductor pattern 82 and does not diffuse into ceramic substrate 81. To achieve good sintering properties for conductor pattern 82 and good electrical properties for ceramic substrate 81, it is preferable that tungsten be present only within conductor pattern 82.
[0069] Figure 13This is a cross-sectional image showing the nickel analysis results for the sample. Nickel is localized in conductor pattern 82 and does not diffuse into ceramic substrate 81. To achieve good sintering properties for conductor pattern 82 and good electrical properties for ceramic substrate 81, it is preferable that nickel be present only in conductor pattern 82.
[0070] Figure 14 8 is a cross-sectional image showing the results of aluminum analysis of the sample. Aluminum is present in both the conductor pattern 82 and the ceramic substrate 81. It is believed that the bonding strength between the conductor pattern 82 and the ceramic substrate 81 is improved.
[0071] Figure 15 This is a cross-sectional image showing the results of silicon analysis of the sample. Silicon is present in both the conductive pattern 82 and the ceramic substrate 81. It was confirmed that the silicon in the ceramic substrate 81 is present only within a range of 10 μm from the interface between the conductive pattern 82 and the ceramic substrate 81 and does not extend beyond this range. Therefore, it is believed that the bonding strength between the conductive pattern 82 and the ceramic substrate 81 is improved without degrading the electrical properties of the ceramic substrate 81.
[0072] Meanwhile, it has been confirmed that when magnesium oxide is used instead of silicon dioxide, a distribution close to the above distribution is obtained, but the amount of magnesium diffusion toward the ceramic substrate 81 is large, and the bonding strength between the conductor pattern 82 and the ceramic substrate 81 is weaker than the bonding strength when silicon oxide is used.
[0073] Figure 16 Bars B1, B2, and B3 shown in the figure show the range of test force [N] when the adhesive strength of the conductive pattern of the sample to be described below was confirmed by a peel test. Bar B1 shows the test result of the conductive pattern formed by using a conductive paste without additives. Bar B2 shows the test result of the conductive pattern formed by using a conductive paste to which 0.5 weight percent of nickel oxide, 1.0 weight percent of aluminum oxide, and 1.0 weight percent of silicon dioxide were added. Bar B3 shows the test result of the conductive pattern formed by using a conductive paste to which 0.5 weight percent of nickel oxide, 2.0 weight percent of aluminum oxide, and 2.0 weight percent of silicon dioxide were added. Due to the addition of aluminum oxide and silicon dioxide, the adhesive strength of the conductive pattern can be improved. In addition, when the content of aluminum oxide and silicon dioxide is increased, the adhesive strength of the conductive pattern can be further improved.
[0074] exist Figure 17In the figure, the solid line shows the relationship between the temperature and the resistance value of the ceramic obtained by firing a raw sheet of aluminum oxide without any sintering agent (hereinafter referred to as additive-free ceramic), and the single-point dashed line shows the relationship between the temperature and the resistance value of the ceramic obtained by firing a raw sheet of a composition containing a sintering agent (hereinafter referred to as additive-containing ceramic). The resistance value of the additive-free ceramic changes little with temperature changes, but the resistance value of the additive-containing ceramic changes more with temperature changes than the additive-free ceramic. That is, the additive-free ceramic has a low temperature dependence of the insulation resistance. As a characteristic required of ceramics for electrostatic chucks, it is expected that the insulation resistance will not decrease too much even when the temperature of the use environment increases. The additive-free ceramic having such a characteristic is effective as a substrate body 21 including an electrostatic electrode 22.
[0075] (Other comparative examples)
[0076] Confirmation of sinterability
[0077] The samples were produced by printing a conductive paste containing 5% by weight of nickel oxide onto a green sheet without a sintering agent and firing them simultaneously. Cross-sectional images of the samples were obtained using SEM (scanning electron microscopy) and EDX (energy dispersive X-ray spectroscopy). The cross-sectional images show that the tungsten crystals in the electrodes become too large after firing. These tungsten crystals easily peel off from the ceramic substrate.
[0078] ·Confirmation of the resistivity of the conductive pattern
[0079] The sample was produced by printing a conductive paste without nickel oxide, aluminum oxide, or silicon dioxide on a green sheet without a sintering agent and firing them simultaneously. The resistivity of the conductor pattern in this sample was 2.85×10 -7 [Ωm].
[0080] The sample was manufactured by printing a conductive paste containing 1 weight percent nickel oxide, 3 weight percent aluminum oxide, and 3 weight percent silicon dioxide on a green sheet without a sintering agent and firing them simultaneously. In this sample, the resistivity of the conductor pattern was 2.84×10 -7 [Ωm], making it possible to obtain a resistivity having the same level as that of the above-mentioned sample.
[0081] The sample was manufactured by printing a conductive paste containing 1 weight percent nickel oxide and 10 weight percent aluminum oxide without adding silicon dioxide on a green sheet without a sintering agent and firing them simultaneously. In this sample, the resistivity of the conductor pattern was 1.24×10 -6 [Ωm], which increases the resistivity.
[0082] According to this embodiment, as described above, the following effects can be obtained.
[0083] (1) The mounting table 20 of the electrostatic chuck 1 includes a substrate body 21 and an electrostatic electrode 22 provided in the substrate body 21. The substrate body 21 is made of ceramic containing aluminum oxide (Al2O3). The electrostatic electrode 22 is a sintered body containing tungsten (W) as a main component and further containing nickel oxide (NiO), aluminum oxide (Al2O3), and silicon dioxide (SiO2). When the electrostatic electrode 22 is formed to have such a configuration, the mounting table 20 including the electrostatic electrode 22 can be obtained without degrading any characteristics of the ceramic of the substrate body 21.
[0084] (2) Nickel oxide improves the sinterability of tungsten. Alumina and silicon dioxide improve the adhesion between ceramic and tungsten. Therefore, there is no need to use any sintering agent. Therefore, the mounting table 20 including the electrostatic electrode 22 can be obtained without degrading any of the ceramic's properties.
[0085] (3) The purity of the ceramic of the substrate body 21 is 99.5% or higher. Such a substrate body 21 has low temperature dependence of insulation resistance and can suppress a decrease in insulation resistance as temperature rises.
[0086] (4) The relative density of the ceramic of the substrate body 21 is 98% or higher. This substrate body 21 has a small number of pores on its front surface and inside. The pores affect the adsorption of the substrate body 21. Therefore, a substrate body 21 with a high relative density is characteristically preferred for the electrostatic chuck 1.
[0087] (Second embodiment)
[0088] Figure 18 is a schematic cross-sectional view of a semiconductor device package according to a second embodiment. Figure 19 is a schematic plan view of a semiconductor device package.
[0089] like Figure 18 As shown, the semiconductor device package 100 has a ceramic substrate 110, a heat sink 150, and external connection terminals 160. The heat sink 150 is soldered to the ceramic substrate 110.
[0090] The ceramic substrate 110 has a plurality of (four in this embodiment) layered ceramic substrates 111, 112, 113, and 114, wiring patterns 121, 122, 123, and 124 made of tungsten, and through-holes 132, 133, and 134 penetrating the ceramic substrates 112, 113, and 114. The through-hole 132 connects the wiring patterns 121 and 122 to each other. The through-hole 133 connects the wiring patterns 122 and 123 to each other. The through-hole 134 connects the wiring patterns 123 and 124 to each other. The ceramic substrate 110 has a substrate body composed of the ceramic substrates 111 to 114 and the wiring patterns 121 to 124 made of tungsten.
[0091] like Figure 18 and Figure 19 As shown, a cavity 170 is provided in the ceramic substrate 110 so as to penetrate the central portion of the ceramic base materials 112, 113, and 114 so that the semiconductor element 200 can be mounted in the cavity 170. The wiring pattern 121 is arranged on the upper surface of the ceramic base material 112 so as to surround the cavity 170. An opening portion 111X is formed in the ceramic base material 111 to expose the wiring pattern 121.
[0092] The ceramic substrates 111 to 114 are made of ceramic containing aluminum oxide. The wiring patterns 121 to 124 and the through-holes 132 to 134 are sintered bodies containing tungsten as a main component and further containing nickel oxide, aluminum oxide, and silicon dioxide. The ceramic substrate 110 can be manufactured by a manufacturing method similar to or the same as that of the mount 20 in the first embodiment.
[0093] In the semiconductor device package 100, the semiconductor element 200 is mounted on the heat sink 150. The pads of the semiconductor element 200 are electrically connected to the wiring patterns 121 of the ceramic substrate 110 through bonding wires or the like. Therefore, the semiconductor element 200 is connected to the external connection terminals 160 through the wiring patterns 121 to 124 and the through-holes 132 and 134.
[0094] In such a semiconductor device package 100, a ceramic substrate 110 including wiring patterns 121 to 124 can be obtained in a manner similar to or the same as that of the first embodiment without degrading the characteristics of the ceramic base materials 111 to 114 forming the substrate body. In the ceramic substrate 110, the adhesion between the ceramic base materials 111 to 114 and the wiring patterns 121 to 124 in the ceramic substrate 110 can be improved.
[0095] (Other embodiments)
[0096] Incidentally, the aforementioned embodiment can be implemented as any of the following embodiments: The electrostatic chuck included in the above-described first embodiment or any one or more components thereof can be appropriately changed.
[0097] The heat sink 23 in the first embodiment described above may be provided between the mounting table 20 and the base plate 10. Alternatively, the heat sink 23 may be provided inside the base plate 10. Alternatively, the heat sink 23 may be attached to the underside of the electrostatic chuck from the outside.
[0098] The electrostatic chuck according to any of the first embodiment and the modified examples can be applied to semiconductor manufacturing equipment such as dry etching equipment (eg, parallel plate type reactive ion etching (RIE) equipment).
[0099] Although the preferred embodiments and the like have been described in detail, the concept of the present invention is not limited to the above-described embodiments and the like, and various modifications and substitutions can be made to the above-described embodiments and the like without departing from the scope of the claims.
[0100] This application claims the benefit of Japanese Patent Application No. 2018-165830, filed on September 5, 2018, and Japanese Patent Application No. 2019-147509, filed on August 9, 2019, which are hereby incorporated by reference herein in their entirety.
Claims
1. A ceramic substrate, comprising: substrate body; as well as a conductor pattern, which is provided in the substrate body, in, The substrate body is made of ceramic containing aluminum oxide, the purity of aluminum oxide contained in the ceramic is 99.5% or more, and The conductor pattern is a sintered body containing tungsten as a main component and further containing nickel oxide, aluminum oxide, and silicon dioxide.
2. The ceramic substrate according to claim 1, wherein: Nickel is located in the electrical conductor pattern.
3. The ceramic substrate according to claim 1, wherein: The ceramic substrate is used for semiconductor device packaging.
4. An electrostatic chuck, comprising: substrate body; as well as an electrostatic electrode disposed in the substrate body, in, The substrate body is made of ceramic containing aluminum oxide, the purity of aluminum oxide contained in the ceramic is 99.5% or more, and The electrostatic electrode is a sintered body containing tungsten as a main component and further containing nickel oxide, aluminum oxide, and silicon dioxide.
5. The electrostatic chuck according to claim 4, wherein: Nickel is located in the electrostatic electrode.
6. The electrostatic chuck according to claim 4, wherein: The electrostatic electrode is a sintered body made of a conductive paste containing tungsten as a main component and further containing nickel oxide, aluminum oxide and silicon dioxide, and In the conductive paste, the amount of nickel oxide added relative to tungsten is in a range of 0.2 weight percent to 1.0 weight percent.
7. The electrostatic chuck according to any one of claims 4 to 6, wherein: The electrostatic electrode is a sintered body made of a conductive paste containing tungsten as a main component and further containing nickel oxide, aluminum oxide and silicon dioxide, and In the conductive paste, the addition amount of aluminum oxide relative to tungsten is in the range of 0.2 weight percent to 3.0 weight percent, and the addition amount of silicon dioxide relative to tungsten is in the range of 0.2 weight percent to 3.0 weight percent.
8. The electrostatic chuck according to any one of claims 4 to 6, wherein: The relative density of the substrate body to ceramics containing only alumina is 98% or more.
9. The electrostatic chuck according to any one of claims 4 to 6, wherein: The average particle size of aluminum oxide contained in the ceramic is in the range of 1.0 μm to 3.0 μm.
10. A method for manufacturing an electrostatic chuck, the electrostatic chuck comprising a substrate body and an electrostatic electrode disposed in the substrate body, the method comprising: preparing a green sheet made of alumina and an organic material without a sintering agent; patterning a conductive paste on the green sheet to form a conductor pattern on the green sheet, wherein the conductive paste contains tungsten as a main component and further contains nickel oxide, aluminum oxide, and silicon dioxide; and The green sheet and the conductor pattern are fired to form the substrate body and the electrostatic electrode, and the purity of aluminum oxide contained in the substrate body is 99.5% or more. 11 . The method according to claim 10 , wherein the amount of nickel oxide added relative to tungsten is in a range of 0.2 weight percent to 1.0 weight percent.
12. The method according to claim 10 or 11, wherein the amount of aluminum oxide added relative to tungsten is in the range of 0.2 weight percent to 3.0 weight percent, and the amount of silicon dioxide added relative to tungsten is in the range of 0.2 weight percent to 3.0 weight percent.
